THEORETICAL AND BASIC ISSUES OF ORGANIZING INTERNATIONAL FESTIVALS - Nurullayeva Zarina (International Journal of Literature and Language Studies, 2026)
This text describes the socio-cultural nature of festivals, their global and national importance, and the role of Uzbekistan's international festivals in promoting the national heritage. In addition to world-famous holidays, the article analyzes the organizational and financial mechanisms and artistic features of the "Boysun Spring" and "Silk and Spices" festivals under the auspices of UNESCO. Also, the reforms implemented in the years of independence in the historical cities of Samarkand, Navoi, Bukhara in terms of development of handicrafts (paper-making, goldsmithing, carpet-making, pottery) and tourism, as well as ensuring the employment of women were considered. The international recognition, export potential and prospects of digitization of the industry of Uzbekistan's music, cinematography, dance ("Lazgi") and Rishton, Gijduvan pottery schools are revealed on a scientific and analytical basis.